Effect of Interest Rates on Stock Returns in The Banking and Real Estate Industries - Yosep Eka Putra; Mega Rahmi (CV. ULIL ALBAB CORP, 2024)
The study aims to explore the effect of interest rates on stock returns in the banking and real estate industries. Quantitative methods with an associative approach are used to explore relationships between certain variables. The data type used is secondary data, namely interest rate, stock return, type of industry, and market capitalization (size). The population in this study is banking companies listed on the Indonesia Stock Exchange and Bank Indonesia from January 1, 2016 to December 31, 2022. The sample selection method used is purposive sampling. The sample data amounted to 16,380 observations, which were monthly data (short-term). The results showed that interest rates significantly negatively influence stock returns, especially in the banking industry, compared to the real estate industry.